RENEWABLE ENERGY RESEARCH IN UZBEKISTAN: PROSPECTS AND CHALLENGES - Suyarov A.O., Sorimsokov U.S., Boliyev A.M; Nurillayev O.U. (Zeta Repository, 2023)
In the world practice, the use of non-traditional energy sources is expanding, but in Uzbekistan this process is developing very slowly. The country’s economy is built on the use of mainly hydrocarbon raw materials, which are mostly used for domestic needs. At the same time, natural gas is exported in ever-increasing volumes. At the same time, Uzbekistan has a great potential for alternative energy sources, which, according to experts, are three times higher than the resources of organic non-renewable fuel. The country has more than 300 Sunny days a year, windswept territories, and mountain rivers that can be used to generate electricity. Such a rich natural potential must be used for its intended purpose, and highly efficient renewable energy sources, whose popularity is growing all over the world, must be widely applied in practice. The article discusses the possibilities of efficient use of alternative energy in Uzbekistan.